A Qualitative Look at Relationships and Social Support Within Criminogenic Environments - Bernhardt, Mindy O'Hara (2018)
Social Support is both a risk or protective factor when determining a person’s likelihood of committing criminal acts. Traditionally viewed, it is beneficial in people’s lives. However, depending on whether the source or provider of support is a criminal or a non-offender it can have either a positive or negative impact on the recipient’s life. This study attempted to ascertain the effect of an additional related concept – the “message” or content of support – when measuring crime outcomes related to social support. Since people in criminogenic environments are subject to competing cultural demands that sometimes overlap (see e.g., Anderson, 1999), it has been postulated that even adherents to mainstream value systems in these environments might present a criminogenic message, while criminals might present a non-criminogenic message. In addition, such environments may engender specific forms of social support not employed in other environments. To determine the extent to which the content of messaging matters apart from the source, I engaged in semi-structured interviews with active offenders, asking them about their perceptions of social support from conforming and non-conforming others and what messages they believed were conveyed. They were also asked about their own intent regarding the messaging and the social support they provided to others. Based on these interviews, it was determined that the message presented could be different than the corresponding identity of the provider of social support, and that these could result in differential effects on attitudes toward offending. In the future, the social support message and the identity of the social support provider should be viewed as separate concepts and measured and analyzed apart to determine their individual effects on future offending and desistance